Literary Titles as Narrative Gateways: Exploring Novels, Drama, and Poetry - Nino Kemertelidze; Meri Giorgadze (European Scientific Journal, ESJ, 2025)
Titles play a pivotal role in literature, serving as both a gateway and a symbolic microcosm of the narrative. This paper examines the role of literary titles as narrative gateways across various genres, including novels, drama, and poetry. By analyzing titles from plays, classic novels, and poetic works, the study explores how titles serve as entry points into the thematic and emotional landscapes of diverse literary forms. Through this exploration, the paper demonstrates the significance of titles in shaping reader expectations and enhancing the interpretive experience across different genres. This study categorizes literary titles into five distinct groups: descriptive titles, misleading titles, revelatory titles, titles borrowed from other literary works, and thematic titles. The study highlights how titles enhance narrative engagement, reflect thematic depth, and create intertextual connections. Through this classification, the paper emphasizes the aesthetic, philosophical, and interpretive dimensions of titles in literary fiction, offering insights into their enduring significance.